Analisis Pengendalian Kualitas Produksi Beras dengan Menggunakan Metode SQC (Statistic Quality Control) di Kilang Padi Pukun Kuala Tanjung - Zainul Anwar; Abdurrozzaq Hasibuan; Siti Rahma Sibuea (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
The Pukun Kuala Tanjung rice factory is a rice factory located in Pematang Tobat village, Sei Suka subdistrict, Batubara district. The Pukun Kuala Tanjung rice factory has been operating for fifteen years in milling rice into rice. In operating the Pukun Kuala Tanjung rice factory, it can produce 25 tons of rice/week. In carrying out the rice production process at the Pukun Kuala Tanjung rice mill, we often find that the rice produced does not match the quality of production, including the color of the rice being less than good (yellow), rice that is not peeled and crushed, which can lead to a decrease in the quality for sale and even unsalability. rice on the market so that the Pukun Kuala Tanjung rice factory experiences losses in producing rice. The aim of this research is as follows: to know how to control the quality of rice using the SQC (Statistical Quality Control) method, to find out the quality of rice produced by the Pukun Kuala Tanjung rice factory is still in good condition. controlled or not. This research uses descriptive quantitative research both when collecting and processing data where the data collected is data on defective rice products and data processing will be carried out using the SQC (Statistica Quality Control) method. From the data processing that has been carried out in this research, the author draws the following conclusions: Rice quality control using the SQC (Statistical Quality Control) method can be seen as follows: Based on the control chart, it is known that defective products are not within the upper control limits (Upper Control Limit) and Lower Control Limit which can mean that a defective product requires repairs to be made to the defective product.